The Accumulation of Heavy Metal (Lead And Copper) in Milkfish (Chanos-Chanos, Forskal) Ponds From Dukuh Tapak, Kelurahan Tugurejo, Semarang - Aniek Suryani Sukowati (Graduate School Bogor Agricultural University (SPs IPB), 2018)
Tapak River pollution that occurred for the last few years will lead to contamination of heavy metals in milkfish ponds located in Tapak area. This finding potentially causes the accumulation of heavy metals (lead and copper) in the water, sediments and organs (gills, liver and muscle) of milkfish and will affect fish productivity and food safety. This study related to the assessment of 2 (two) heavy metal accumulation in aquatic pond environment and the maximum limit of fish consumption based on Provisional Tolerable Weekly Intake (PTWI) and Estimated Weekly Intake (EWI) adopted from Turkmen (2009) and Elnabris (2013). The objectives of this study were to : (1) analyze the concentration factor of heavy metal in sediment and bioconcentration factor (BCF) of heavy metals in milkfish organ and (2) determine maximum tolerance limits for milkfish to be consumed. The concentration factor of heavy metal distribution in the sediments showed that the range of heavy metal content in the sediments was 1001.793± 143.573 – 6679.003±825.832 times compared to the heavy metal content in the column water. The calculation result of the average bioconcentration factor (BCF) of heavy metal (water) in each fish organ exhibited that Pb metal tended to be highly accumulative in all fish organs while Cu was low to high in accumulative. The BCF value of heavy metals (sediments) towards milkfish organ showed that Pb and Cu were slightly accumulative. The assessment results of EWI showed that the fish muscle was still suitable for adult consumption with a limit of 0.624 kg/week while the liver of milkfish was not suitable for consumption. Meanwhile, children were not allowed to consume milkfish from Tapak ponds.